Brain angiogenic gene expression in fetuses with congenital heart disease. (2nd November 2018) - Sánchez, O.; Ruiz‐Romero, A.; Domínguez, C.; Ferrer, Q.; Ribera, I.; Rodríguez‐Sureda, V.; Alijotas, J.; Arévalo, S.; Carreras, E.; Cabero, L.; Llurba, E.
ABSTRACT: Objective: To assess potential differences in the expression of antiangiogenic and angiogenic factors and of genes associated with chronic hypoxia in cerebral tissue of euploid fetuses with congenital heart disease (CHD) vs those without. Methods: Cerebral tissue was obtained from 15 fetuses with CHD and 12 control fetuses that had undergone termination of pregnancy. Expression profiles of the antiangiogenic factor soluble fms‐like tyrosine kinase‐1 (sFlt‐1), the angiogenic vascular endothelial growth factor‐A (VEGF‐A) and placental growth factor (PlGF), and of genes associated with chronic hypoxia were determined by real‐time polymerase chain reaction in tissue from the frontal cortex and the basal ganglia of the fetuses. Results: Expression of sFlt‐1 was 48% higher in the frontal cortex ( P = 0.0431) and 72% higher in the basal ganglia ( P = 0.0369) of CHD fetuses compared with controls. The expression of VEGF‐A was 60% higher ( P = 0.0432) and that of hypoxia‐inducible factor 2‐alpha was 98% higher ( P = 0.0456) in the basal ganglia of CHD fetuses compared with controls. No significant differences were observed between the two groups in the expression of PlGF and hypoxia‐inducible factor 1‐alpha. Conclusion: An overall dysregulation of angiogenesis with a net balance towards an antiangiogenic environment was observed in the cerebral tissue of fetuses with CHD, suggesting that these fetuses may have an intrinsic angiogenic impairment that could contribute to impaired brain perfusion and abnormal neurological development later in life. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.